2011
DOI: 10.5897/ajmr11.094
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermodynamics of high level β-glucosidase production by mutant derivative of Aspergillus niger under submerged growth conditions

Abstract: Gamma rays mediated mutagenesis and subsequent selection on 2-deoxy-D-glucose developed a highly catabolite de-repressed and stable β-glucosidase (BGL) hyper-producer mutant of local Aspergillus niger NIBGE, which has high potential for industrial applications. The M6 mutant showed highest constitutive production of BGL (14,900 IU/L) on glucose as compared to control (5,900 IU/L). Wheat bran was the best carbon source and BGL production by parent and mutant strain was 16,200 and 29,500 IU/L, respectively. Effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Nagar and others found elevated production of cellulase-poor alkali stable xylanase by Bacillus pumilus SV-85S in the presence of WB under SSF [40]. The enzyme was entirely stable over a wide pH (5)(6)(7)(8)(9)(10)(11) interval and maintained 52% of its efficacy at a temperature of 70 • C for 30 min. Approximate evaluation of price collation showed that the price of the enzyme generation using WB was reduced to 50%.…”
Section: Ssf Smfmentioning
confidence: 98%
See 3 more Smart Citations
“…Nagar and others found elevated production of cellulase-poor alkali stable xylanase by Bacillus pumilus SV-85S in the presence of WB under SSF [40]. The enzyme was entirely stable over a wide pH (5)(6)(7)(8)(9)(10)(11) interval and maintained 52% of its efficacy at a temperature of 70 • C for 30 min. Approximate evaluation of price collation showed that the price of the enzyme generation using WB was reduced to 50%.…”
Section: Ssf Smfmentioning
confidence: 98%
“…Substrate for enzymes production [5] As an inducer for enzymes Complex substrate [9][10][11] Production of protease, amylase, and glucoamylase Nitrogen source [5] Metabolites Bacitracin Cyclosporine-A Gibberellic acid Cheap raw material [12][13][14] Biofuel Bioethanol Biobutanol Biohydrogen…”
Section: Enzymesmentioning
confidence: 99%
See 2 more Smart Citations